ШУТИС-ийн Физикийн Сургалтанд Нэвтрүүлж Буй Ажлын Үр Дүн Г.Зоригт, Ч.Алдармаа, Г.Мөнхсайхан - Г, Зоригт; Ч, Алдармаа; Г, Мөнхсайхан (Scientific transaction of the National University of Mongolia. Physics, 2022)
This paper is based on results of new methodology of organizing general physics course that have been taught at the MUST. The results are based on last 9 years’ experiences on effective way seminar and self-assignment for engineering students of SICT, MUST. The research shows that regular testing method in every seminar classes has affected on increase of study activities of students corresponding to increase of the quality. The distribution curve of the 70 and 30 points shows that the number of students with high grading has increased within the years.